2015
DOI: 10.1556/030.62.2015.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecological tolerance of bacteria isolated from the rhizosphere of halophyton plants living nearby Kiskunság soda ponds, Hungary

Abstract: Many halophytes and halophilic microorganisms are capable to adapt to the extremities of saline habitats. This study reveals the taxonomic diversity and ecological tolerance of bacteria isolated from the rhizosphere of three different halophytes (Bolboschoenus maritimus, Puccinellia limosa and Aster tripolium) living in the vicinity of Kiskunság soda ponds. Following a sampling in September 2013, altogether 76 bacterial strains were isolated using two different media. The strains were identifi ed on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(40 reference statements)
1
9
0
2
Order By: Relevance
“…While community composition also seemed to vary, differences were not significant (Table 2). Halomonas was the dominant genera in Halocnemum strobilaceum communities (32.4% of total abundance), a significantly higher proportion than in the other plant-associated communities; this trend is consistent with previous studies (Al-Mailem et al, 2010; Marasco et al, 2016), including of other halophytes (Borsodi et al, 2015). In the Halostachys caspica rhizosphere, Exiguobacterium was the most common genus, followed by Citrobacter , Acinetobacter and Pseudomonas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While community composition also seemed to vary, differences were not significant (Table 2). Halomonas was the dominant genera in Halocnemum strobilaceum communities (32.4% of total abundance), a significantly higher proportion than in the other plant-associated communities; this trend is consistent with previous studies (Al-Mailem et al, 2010; Marasco et al, 2016), including of other halophytes (Borsodi et al, 2015). In the Halostachys caspica rhizosphere, Exiguobacterium was the most common genus, followed by Citrobacter , Acinetobacter and Pseudomonas.…”
Section: Discussionsupporting
confidence: 91%
“…These studies have revealed that bacterial communities in the halophyte rhizosphere are distinctly different from those of non-halophytic plants, containing a larger proportion of halophilic bacteria (Al-Mailem et al, 2010). Many halophilic bacteria have been identified or isolated from halophyte roots, soils and desert habitats, including species belonging to the following genera: Alkalimonas , Bacillus , Brachybacterium , Brevibacterium, Cronobacter , Halobacillus , Halomonas , Marinococcus , Methylibium , Nesterenkonia , Oceanobacillus , Staphylococcus , Stenotrophomonas , Virgibacillus and Zhihengliuella (Sgroy et al, 2009; Siddikee et al, 2010; Tang et al, 2011; Shi et al, 2012; Zhou et al, 2012; Ramadoss et al, 2013; Borsodi et al, 2015; Zhao et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Zab-szék, Kelemen-szék és Böddi-szék körüli növényzet rhizoszférájából származó baktériumtörzsek só-és pH-toleranciájával foglalkozó eredményeket korábban BORSODI et al (2015) közölték. BÁRÁNY et al (2014 ugyanezen három területről származó néhány növényfaj rhizoszférájából származó minták mikrobaközösségeinek genetikai és katabolikus ujjlenyomatát hasonlították össze, utóbbit a fent említett MicroResp módszerrel.…”
Section: Bevezetésunclassified
“…Ráadásul az ingadozó hőmérséklet és vízjárás, a kiszáradástól az időszakos vízborításokig tovább fokozzák a környezeti szélsőségeket. Vizsgálatainkat 2013-ban kezdtük a Kiskunsági Nemzeti Park szikes területein, amelynek első eredményeit már közöltük (BÁRÁNY et al 2014;BORSODI et al 2015).…”
unclassified